2017
DOI: 10.1155/2017/9241238
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Mortality among Multidrug-Resistant Tuberculosis Patients in Tanzania

Abstract: Problem Factors related to MDRTB mortality in Tanzania have not been adequately explored and reported. Objectives To determine demographic, clinical, radiographic, and laboratory factors associated with MDRTB mortality in a Tanzanian TB Referral Hospital. Methodology This was a cross-sectional study with 193 participants. Demographic, clinical, laboratory, and radiological data were collected, and their associations with mortality among MDRTB patients were determined. Results and Conclusions Cough was the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 26 publications
(31 reference statements)
10
22
1
1
Order By: Relevance
“…This study found that incidence of mortality was 8.2 per 1000 person-months observation. This finding was comparable with previous studies conducted in Ethiopia [14,18], and other countries in sub-Saharan Africa [23]. In contrary, our finding was higher compared to the research conducted in St. Peter specialized TB hospital in Addis Ababa which is 3.6 per 10,000 person-days [13].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study found that incidence of mortality was 8.2 per 1000 person-months observation. This finding was comparable with previous studies conducted in Ethiopia [14,18], and other countries in sub-Saharan Africa [23]. In contrary, our finding was higher compared to the research conducted in St. Peter specialized TB hospital in Addis Ababa which is 3.6 per 10,000 person-days [13].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, understanding risk factors for DR-TB mortality is vital to improving DR-TB treatment outcomes. Previous studies have shown that increasing age [15,16], smoking cigarette [17,18], comorbidities [19][20][21] such as HIV/AIDS and diabetes, clinical complication [14,21,22] therapeutic delay [3,23,24] were contributing factors for DR-TB mortality .…”
Section: Introductionmentioning
confidence: 99%
“… 25 One recent study showed that smoking and HIV infection were significant risk factors for mortality in patients with MDR-TB. 26 When smokers quit smoking, the risk of death due to tuberculosis drops significantly (by 65% compared with that observed for those who continue smoking), which indicates that smoking cessation is an important factor in reducing tuberculosis-related mortality. 25 …”
Section: Risk Factors For Tuberculosismentioning
confidence: 99%
“…It is found that smoking reduces body immune. Not only it worsens the TB condition to become resistant to medications, it also leads to the risk of recurrence when TB has been treated (Mollel and Chilongola, 2017). As the result of severity level on smoking group, it may generate the increasing risk of resistance to medications therefore it increase mortality rate.…”
Section: The Association Between Smokingmentioning
confidence: 99%